Netnography Study of Mental Health Disorder Discussion in the K-Pop Music Video among YouTube Users - Alya Syahputri; Heidy Arviani; Roziana Febrianita; Zainal Abidin Achmad (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2023)
Mental health is one of the important aspects of realizing overall health. Few people with mental health disorders are treated due to a lack of education about mental health in society. Education about mental health needs to be done to be able to change the bad stigma against people with mental health disorders. Mental health education can be done by with any media, one of which is with music and music videos. Many musicians, like Korean musicians, bring up the topic of mental health in their songs. The researcher wanted to examine how messages related to mental health were conveyed by YouTube users in the comment section on Lee Hi’s music video entitled HOLO and Sunmi’s titled Borderline. This study aims to look at and map mental health issues from the two music videos. This research uses a type of descriptive qualitative research and netnography research method, using observation and documentation. The results of this study indicate that there are several types of mental health issues written by YouTube users in the two music video comment sections.